Ovarian cancer survival by stage, histotype, and pre-diagnostic lifestyle factors, in the prospective UK Million Women Study. (February 2022) - Gaitskell, Kezia; Hermon, Carol; Barnes, Isobel; Pirie, Kirstin; Floud, Sarah; Green, Jane; Beral, Valerie; Reeves, Gillian K.; ,
Abstract: Background: Ovarian cancer is the fifth leading cause of cancer mortality in UK women. Ovarian cancer survival varies by disease stage at diagnosis, but evidence is mixed on the effect of tumour histological type (histotype) and other factors. Methods: 1.3 million UK women completed a detailed health questionnaire in 1996–2001 and were followed for incident cancers and deaths via linkage to national databases. Using Cox regression models, we estimated adjusted relative risks (RRs) of death from ovarian cancer, by stage at diagnosis, tumour histotype, and 16 other personal characteristics of the women. Results: During 17.7 years' average follow-up, 13, 222 women were diagnosed with ovarian cancer, and 8697 of them died from the disease. Stage at diagnosis was a major determinant of survival (stage IV vs I, RR=10.54, 95% CI: 9.16–12.13). Histotype remained a significant predictor after adjustment for stage and other factors, but associations varied over the follow-up period. Histotype-specific survival was worse for high-grade than low-grade tumours. Survival appeared worse with older age at diagnosis (per 5 years: RR=1.19, 95% CI: 1.15–1.22), higher BMI (per 5-unit increase: RR=1.06, 95% CI: 1.02–1.11), and smoking (current vs never: RR=1.17, 95% CI: 1.07–1.27), but there was little association with 13 other pre-diagnostic reproductive, anthropometric, and lifestyle factors. Conclusion: Stage at diagnosis is a strong predictor of ovarian cancer survival, but tumour histotype and grade remain predictors of survival even after adjustment for stage and other factors, contributing further evidence of biological dissimilarity between the ovarian cancer histotypes. Obesity and smoking represent potentially-modifiable determinants of survival, but the stronger association with stage suggests that improving earlier diagnosis would have a greater impact on increasing ovarian cancer survival. Highlights: This study investigated ovarian cancer survival in a cohort of 1.3 million UK women. After 18 years of follow-up, the study included 13, 222 incident ovarian cancers. Stage, age and histotype were significantly associated with ovarian cancer survival. Survival was also worse with higher BMI and smoking, but with less impact than stage.